Comparison of the efficiency of diluents on the enumeration of molds contaminated in spices and spice products - Theparoonrat, Supannee; Keawchom, Sulawadee (Bulletin of Applied Sciences, 2022)
Fungal contamination of spices and spice products was critical problem for quality assurance of Thai food. Antifungal activity of spices caused underestimation on mold contamination. This study was aimed to improve the efficiency of enumeration of mold in spices and spice products. A total of 17 samples including 12 spices: dried chilli (2), pepper(2), clove (2), turmeric (1), Chinese star (2), coriander seeds (1), and cinnamon (2), and 5 spice products (green curry paste, mussaman curry paste, red curry paste, southern yellow curry paste, and Indian-style curry paste were subsequently examined on five diluents containing neutralizing agent : F1 (Bacteriological peptone 1 g/, Tween 80 30 m/1, L-00-Phosphatidylcholine : Lecithin 0.7 g/),F2(Bacteriological peptone 13/1, Tween 80 5 m/1, L-00-Phosphatidylcholine: Lecithin 7 g/1, Sodium thiosulfate 69/1, Sodium bisulfate 2.5 g/0), F3 (Fluid casein digest soya lecithin medium with polysorbate 20 40 mV/), F4 (L-Histidine 19/1, Tween 80 30 ml/l, L-O-Phosphatidylcholine 3 g/) and F5 (D/E Neutralizing broth (Himedia) The sample were cultured on plating culture media dichloran rose-bengal chloramphenicol agar (DRBC). The most effective diluents which inhibited antifungal properties of spices were F4 or F5, demonstrated by the average number of mold colonies of these formulas gave significantly higher than 0.1% peptone (control). In conclusion, the usage of F4 or F5 formulas as diluent incorporated with DRBC agar is an effective method for enumeration of mold in spices and spice products.